Phase distribution and magnetic properties of hard/soft ferrite nanocomposites prepared through mechanical alloying and physical mixing method - Ahmad, Aisyah Radhiah (2019)
Nanocomposite magnet consisting of hard and soft magnetic phases has attracted many attentions from the researcher in recent years. The exchange coupling between hard and soft phase can combine the high coercivity of the hard phase and the high magnetization of soft phase to produce a magnet with high energy product. The mechanical alloying and physical mixing method are chosen to produce the nanocomposite. The hard phase, SrFe12O19 and soft phase, Ni0.5Zn0.5Fe2O4 were mixed to become nanocomposite SrFe12O19/Ni0.5Zn0.5Fe2O4. The effect of phase distribution in the nanocomposite is studied by varying the amount of soft ferrite. While the amount of hard ferrite is kept constant. The novelty of this research lies in the different phase distribution between hard and soft phases in the nanocomposite, which gives more understanding of the effect of phase distribution on the exchange coupling. The characterizations of the samples are carried out using Thermogravimetric Analysis (TGA), X-ray Diffraction (XRD), Vibrating Sample Magnetometer (VSM), Electron Paramagnetic Resonance (EPR) and microstructure analysis using Transmission Electron Microscope (TEM) and Field Emission Scanning Electron Microscope (FESEM). The XRD results on the nanocomposites shown that both hard phase, SrFe12O19 and soft phase, Ni0.5Zn0.5Fe2O4 are present in the samples producing the SrFe12O19/Ni0.5Zn0.5Fe2O4 nanocomposite. From the mechanical alloying method, the nanocomposites with 10-20 wt.% of soft phase content shown the remanence ratio, Mr/Ms ≥ 0.5. The best result is from nanocomposite with 20 wt.% soft phase with the values of Hc and Ms are 3313.7 G and 36.3 emu/g, respectively. While, for physical mixing, the nanocomposites with 10-30 wt.% of soft phase content shows Mr/Ms ≥ 0.5. With the best result is from nanocomposite ferrite with 30 wt.% soft phase with the values of Hc and Ms are 2926.3 G and 45.5 emu/g, respectively. We also manage to get the average particle size for the nanocomposites < 50 nm for both methods. From the results, it is found that the exchange coupling in the nanocomposites is affected by the phase distribution between the hard and soft phases as the amount of soft phase increase in the nanocomposite, the coercivity and magnetization decrease. For example, the magnetization for the nanocomposites prepared by physical mixing method decrease from 45.5 to 5.0 emu/g for nanocomposite with 30-100 wt.% of soft phase content. The optimum amount of soft phase needed in the nanocomposite is found to be 20-30 wt.% to maximize the effect of the exchange coupling between the hard and soft ferrites.